Persistent influence of the North Atlantic hydrography on central European winter temperature during the last 9000 years - Mangini, Augusto; Verdes, P.; Spötl, Christoph; Scholz, Denis; Aeschbach, Nicole; Kromer, Bernd (Geophysical research letters, 2007)
A prominent feature of the N. Atlantic's Holocene climate is a series of centennial and millennial shifts in ocean surface hydrography (Bond et al., 2001; Oppo et al., 2003). Here, we compare a climate reconstruction from the Central Alps for the last 9,000 years derived from the oxygen isotope record in stalagmites with the percentage of hematite-stained-grains in N. Atlantic sediments, an indicator for the proportion of ice-bearing surface water from north of Iceland. The excellent match between the two curves proves that meteorological conditions in the Alpine region responded synchronously to changes in the hydrography of the N. Atlantic during winter. In addition, the speleothem record suggests significant multi centennial and millennial variability of N. European winters throughout the past 9,000 years that might have been incompletely recorded in tree-ring archives.
Online veröffentlicht: 18. Januar 2007
Gesehen am 22.12.2025